On the Effects of Task Load Involvement on Iranian Intermediate EFL Learners Word Learning: Reading and writing Tasks vs. Translation Tasks - Samaneh Yazdani (Journal of Modern Research in English Language Studies)
Due to the fact that all language learners and teachers are aware of the fact that acquiring a second language involves a learning of the large number of vocabulary items, investigating how vocabulary is learned and what the best ways are to enhance effective acquisition have been important lines of investigation in the field of second language acquisition (SLA). The present study intended to compare the effect of enhancing the quality of vocabulary acquisition by reading, writing, and translation tasks with different degrees of involvement load. To this end, 60 intermediate third grade junior high school students were randomly assigned to four groups. In each group a task with a different level of involvement, including two different reading tasks, a writing task, and a translation task was instructed over a six-month period. The results of the descriptive statistics and one-way ANOVA revealed that the group with the highest involvement load task outperformed the other groups in terms of vocabulary acquisition, but the translation task even led to a greater performance in the post-test. These unique findings shed some light on the importance and the practicality of translation tasks in ESL contexts.